HUBUNGAN PENGETAHUAN DAN SIKAP REMAJA PUTRI TERHADAP PRILAKU PENANGANAN DISMENORE DI SMPN 1 WIH PESAM KABUPATEN BENER MERIAH - Simah Bengi, Seftia; Yusran, Mawadhah; HS, Nurlaely (Jurnal Ilmiah Cerebral Medika, 2024)
ABSTRACT Dysmenorrhea or dysmenorrhea in Indonesian means pain during menstruation. In BenerMeriah Regency, especially at SMP N 1 Wih Pesam which consists of 334 female students. Where only 20 of the 134 female students from grade 9 did not experience dysmenorrhea, 10 of the 99 female students from grade 8, and 7 of the 101 female students from grade 7. The rest experienced pain during menstruation or what we often call dysmenorrhea. This research aims to find out "the relationship between knowledge and attitudes of young women towards dysmenorrhea management behavior at SMPN 1 Wih Pesam, Bener Meriah Regency in 2023". This type of quantitative research uses an analytical survey research design with a cross sectional approach. The sampling technique was carried out using simple random sampling with a sample size of 67 samples. This research instrument uses a questionnaire. This research was conducted at SMPN 1 Wih Pesam, Bene rMeriah Regency on July 17 2023. The results of the research showed that the relationship between daughters' knowledge and dysmenorrhea handling behavior was obtained with a p-value of 0.009, while the relationship between daughters' attitudes towards dysmenorrhea treatment behavior was obtained. p-value 0.000. It can be concluded that there is a relationship between knowledge and attitudes of young women towards the behavior of handling dysmenorrhea at SMPN 1 Wih Pesam, Bener Meriah Regency in 2023. It is recommended that health service institutions will be able to provide more education to young women regarding dysmenorrhea and maintain consistency in socializing. Keywords : Level of knowledge, Attitude, Management of Dysmenorrhea